Structure and genetic diversity of Cedrela (Meliaceae) on the upper Parana river - Huamán Mera, Alexander (2014)
Cedrela (Meliaceae) is a monophyletic genus and includes 17 tree species in the Neotropics. Its diversification intensified in the Late Miocene and Early Pliocene. Most Cedrela species have restricted distribution ranges, however Cedrela fissilis Vell. is widespread. In Brazil C. fissilis Vell. occurs associated with Seasonal and Moist Forest. This species is "endangered" on the red list of the IUCN. Cedrela fissilis is formed by Cedrela fissilis Vell. and Cedrela odorata L., two phylogenetic lineages that are not a monophyletic clade, comprising moreover sequences of C. balansae, called C. fissilis complex. The upper Paraná River spreads into the Cerrado, an important biodiversity hotspot; it is probably remained stable and formed a single large Cerrado refugium during the late Pleistocene, where occurred important climatic changes that could influence in the spread of species. Molecular tools will contribute for understanding the historical process of gene dispersal since the Pleistocene. Seasonal forests are strong threatened ecosystems. The knowledge about seasonal forest has been increased since they are considered as areas of endemism. The aim of this study was to characterize the genetic diversity within and among populations of Cedrela along upper Parana River. Ten microsatellites were used to genotype 192 individuals, then it was obtained high values of heterozygosis (HO=0.65, HE=0.78), with positive values of FIS (FIS=0.18). For AMOVA, 84.93% of the variation were within populations and 15.07% were among populations which also reflected into the values of genetic divergence (FST=0.151). The Cedrela fissilis lineage 1 group showed more diverse, with 22 of 54 private alleles found. It presented FST value (FST=0.111) lower than the populations of Cedrela sp. group (FST=0.188). It has been found strong population structure showing a number of groups equal to five and being greater than the number of known phylogenetic lineages based on DNA sequences and also greater than the results of study of the C. fissilis complex using SSR markers. Three of these five groups are new lineages that no was found in previously works. This suggests, according our evidence, the presence of refugia in the upper Paraná River basin, moreover of a new genetically distinct unit and two more for botanical review. Furthermore, some populations showed conservation relevance of habitat due to the presence of peculiar genetic material and historical process.